Implications of Unlawful Actions by Directors Using the Name of a Limited Liability Company Without Going Through a GMS in Carrying Out Personal Debt Borrowings - Dwi Andika , Dery; Farma Rahayu , Mella Ismelina (Dinasti Research, 2024)
This article is entitled Implications of unlawful acts by directors who use the name of a limited liability company without going through a GMS using normative juridical research methods, with a statute approach and a conceptual approach. The results of the analysis are the implications of unlawful actions by directors who use the name of a limited liability company without going through a GMS in borrowing personal debts, which do not provide binding legal force in terms of collection from the Limited Liability Company, because the conditions for the validity of the agreement are something that is halal or does not conflict with the law. The invitation was not fulfilled, because in the regulations it is stated that carrying out important policies and steps for a company requires making a request for the EGMS to be implemented. However, the debt and receivables agreement remains personally binding on the directors who incur the debt